The intake and performance of dairy ewes fed with different levels of olive cake silage in late pregnancy and suckling periods - Cabiddu A.; Canu M.; Decandia M.; Molle G.; Pompel R. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Five weeks before parturition, 27 Sarda dairy ewes were allotted to 3 groups fed with grass hay, concentrates, and 0 (S0), 250 (S250) and 500 (S500) g of dry matter (DM) per head and day of crude olive cake silage (OCS). In S250 and S500, grass hay was substituted by OCS to have the same level of DM. Treatments were discontinued 5 weeks after lambing. Total intake decreased along with the increase of OCS in the diet. The dry matter disappearance (DMD) of the diets was higher in S0 and S250 than S500. The ewes live weight decreased more in S250 and S500 than S0. Milk production during suckling and milk chemical composition showed no significant effect of treatments. Milk production averaged 1602, 1665 and 1471 ml per head per day, in S0, S250 and S500, respectively. Lamb daily growth was unaffected by the treatments. In conclusion, despite the drop of intake, ewes' performances were not significantly affected by the substitution of grass hay with OCS.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)